Karakteristik Petani dan Kontribusi Hutan Kemasyarakatan (HKm) Terhadap Pendapatan Petani di Kulon Progo - Indah Novita Dewi; San Afri Awang; Wahyu Andayani; Priyono Suryanto (Fakultas Kehutanan Universitas Gadjah Mada, 2018)
Salah satu program yang dikeluarkan Kementerian Kehutanan terkait pemberdayaan masyarakat adalah program Hutan Kemasyarakatan (HKm), yang salah satunya berlokasi di Kabupaten Kulon Progo. Penelitian ini bertujuan untuk mengetahui karakteristik sosial ekonomi petani HKm Kulon Progo dan kontribusi HKm terhadap pendapatan petani. Penelitian dilakukan mulai November 2013 sampai dengan Februari 2014. Data dikumpulkan melalui survei dan wawancara kepada anggota kelompok tani dan dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukkan petani HKm rata-rata berusia 53 tahun, pendidikan petani rendah karena 53% lulusan SD. Rata-rata jumlah tanggungan keluarga 4 orang. Rata-rata luas lahan andil 2.128 m2 dan rata-rata luas lahan milik 2.947 m2 sehingga termasuk petani gurem. Tujuh puluh persen petani HKm hutan produksi dan 47,3% petani HKm hutan lindung masuk ke dalam kategori miskin sekali dan miskin. Kontribusi HKm pada pendapatan petani adalah 6,4% pada hutan produksi dan 4,8% pada hutan lindung. Kecilnya kontribusi dari HKm berimplikasi pada upaya peningkatan pendapatan petani melalui pengembangan potensi tanaman empon-empon dan umbi-umbian serta potensi wisata. Characteristic of Farmer and Contribution of Community Forestry to Farmer’s Income in Kulon ProgoAbstractOne of the project that is held by Ministry of Forestry is Community Forestry (CF), which one is located in Kulon Progo. This research aim was to obtain the social-economic characteristic of CF farmers in Kulon Progo and to know the contribution of CF to their total earning. The data collection had been held from November 2013 until February 2014 and was collected by survey and interview to some members of CF groups. The data was analyzed by descriptive qualitative method. The results showed that the average of farmer’s age was 53; farmer’s education was in a low level as 53% were graduated from elementary school. The average of family member were 4 persons. The average of CF land was 2.128 m2 and the average of farmers’s own land was 2.947 m2. That was meant that the farmer was near to be categorized as poor farmer. Seventy percent of farmers from production forest and 47.3% farmers from protected forest were categorized as very poor and poor. CF contribution towards farmer’s income was 6.4% in production forest and 4.8% in protected forest. The low contribution of CF implicated to improve farmer’s income through developing non-timber forest product asherbs and edible root and also potential for eco-tourism.